ChemInform Abstract: Inorganic Chemistry Solutions to Semiconductor Nanocrystal Problems. Issue 48 (2nd December 2014) - Alvarado, Samuel R.; Guo, Yijun; Ruberu, T. Purnima A.; Tavasoli, Elham; Vela, Javier
Abstract Review: 126 refs.